Black shale ore of Big Karatau is a raw material source of rare and rare earth elements - Muhammad Noorazlan Abd Azis (Tanjong Malim, 2021)
Black shale ore of Big Karatau is a raw material source of rare and rare earth elements by Muhammad Noorazlan Abd Azis